The Cosmological Argument: A Newtonian Challenge to Hume - Granado, Michael (Circumscribere International Journal for the History of Science, 2016)
Hume’s arguments against the cosmological argument have, in the past century, often been highly praised by commentators such as H.D.Aiken and E.C. Mossner. While Hume’s argument often receives strong philosophical support, the four major objections raised against the cosmological argument in book IX of his Dialogues hinge upon a misunderstanding of Newtonian natural philosophy. Hence, when the proper historical context is considered, Hume’s objections are weak at best, for they assume an understanding of matter and physical necessity that are inconsistent with Newtonian natural philosophy. This paper will outline Hume’s objections, and explore how the formulation of the cosmological argument put forth by the English philosopher Samuel Clarke was reliant upon the best available scientific evidence, i.e. Newtonian philosophy. Consequently, any contemporary supporter of Hume who believes that his argument was successful in quenching the enlightenment era reiteration of the cosmological argument does so anachronistically.